2020
DOI: 10.3892/ol.2020.11989
|View full text |Cite
|
Sign up to set email alerts
|

PLAC8 inhibits oral squamous cell carcinogenesis and epithelial-mesenchymal transition via the Wnt/β-catenin and PI3K/Akt/GSK3β signaling pathways

Abstract: Placenta-specific 8 (PLAC8) is closely associated with the proliferation, apoptosis and autophagy of several tumor cells. However, the expression and function of PLAC8 in oral squamous cell carcinoma (OSCC) remain unknown. Therefore, the present study investigated the function and mechanism of PLAC8 in OSCC. Reverse transcription-quantitative PCR and western blot analyses were performed to quantify the expression of PLAC8 in OSCC cell lines. The function of PLAC8 in OSCC was investigated via transfection, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…OSCC has many steps, such as carcinogenesis, progression, invasion, EMT and metastasis (85). PI3K/Akt pathway is known to play important roles in controlling all these steps (86)(87)(88)(89). The potential targets of miR-155-5p includes PTEN (90) and SHIP1 (91), both of which negatively regulate PI3K/Akt signaling pathway (90,92).…”
Section: Discussionmentioning
confidence: 99%
“…OSCC has many steps, such as carcinogenesis, progression, invasion, EMT and metastasis (85). PI3K/Akt pathway is known to play important roles in controlling all these steps (86)(87)(88)(89). The potential targets of miR-155-5p includes PTEN (90) and SHIP1 (91), both of which negatively regulate PI3K/Akt signaling pathway (90,92).…”
Section: Discussionmentioning
confidence: 99%
“…Effects followed with decreased PVT1 in villi samples might be involved in RSM pathogenesis, rendering PVT1 as a therapeutic target [199]. PLAC8, a newly-explored factor in tumorigenesis, has been regarded as a target of treating oral squamous cell carcinoma for its regulatory roles in ERK [201], Wnt/β-catenin and PI3K/Akt/GSK3β pathways [202], respectively. In trophoblasts, PLAC8 co-localizes with p53 and mediates its degradation, facilitating the viability, proliferation and differentiation via enhanced autophagy [106].…”
Section: Potential Therapeutic Methods Targeting Autophagy For Smmentioning
confidence: 99%
“…Studies have shown that PLAC8 overexpression contributes to MAPK pathway activation and metastatic phenotypes [92] and that PLAC8 plays a role in the epithelial-mesenchymal transition [93] in different types of cancer. PLAC8 promotes trophoblast cell, non-small cell lung cancer cell, and clear cell renal cell carcinoma invasion and migration [17,88,94,95]. However, PLAC8 inhibits oral squamous cell invasion [95].…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…PLAC8 promotes trophoblast cell, non-small cell lung cancer cell, and clear cell renal cell carcinoma invasion and migration [17,88,94,95]. However, PLAC8 inhibits oral squamous cell invasion [95]. PLAC8 reflects the expression of epithelial-mesenchymal related markers including E-cadherin, N-cadherin and vimentin thus involving epithelialmesenchymal transition process.…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%